41.6k views
3 votes
HELPPPPP !!!

What is the justification for the step taken from line 2 to line 3?

3x +9-7X=X+10+X

-4x+9 = 2x+10

-6x+9= 10

-6x=1

x = 6 음

(A) the subtraction property of equality

(B) the multiplication property of equality

(C) combining like terms on one side of the equation

(D) the distributive property

Submit

User Fulatoro
by
5.3k points

2 Answers

5 votes

A. the subtraction property of equality

User Blispr
by
5.4k points
2 votes

Answer:

(A) the subtraction property of equality

Explanation:

Given

The steps in the question

Require

Justify step 2 to 3

Write out step 2:


-4x+9 = 2x+10

Apply subtraction property by subtracting 2x from both sides


-4x-2x+9 = 2x-2x+10


-6x+9 = 10

Notice that the above equation is represented in step 3.

Hence, option A answers the question.

User Axa
by
5.1k points